Neglect and aphasia in the acute phase as predictors of functional outcome 7 years after ischemic stroke. (13th September 2017) - Gerafi, J.; Samuelsson, H.; Viken, J. I.; Blomgren, C.; Claesson, L.; Kallio, S.; Jern, C.; Blomstrand, C.; Jood, K.
Abstract : Background and purpose: Visuospatial inattention (VSI) and language impairment (LI) are often present early after stroke and associations with an unfavorable short‐term functional outcome have been reported. The purpose of this study was to investigate whether a screening of VSI and LI as indicators of cortical symptoms early after stroke could predict long‐term functional outcomes. Methods: A consecutive cohort of 375 patients with ischemic stroke was assessed for the occurrence of VSI at a median of 7 days after admission (interquartile range, 1–5 days) using the Star Cancellation Test and for LI (within the first 7 days) with the language item in the Scandinavian Stroke Scale. Seven years later, functional outcomes were assessed by the modified Rankin scale and Frenchay Activities Index in 235 survivors without recurrent stroke. Relationships between baseline predictors and functional outcome at 7 years were analyzed with bivariate correlations and multiple categorical regressions with optimal scaling. Results: The regression model significantly explained variance in the modified Rankin scale ( R 2 = 0.435, P < 0.001) and identified VSI ( P = 0.001) and neurological deficits ( P < 0.001; Scandinavian Stroke Scale score without the language item) as the significant independent predictors. The model for Frenchay Activities Index was also significant ( R 2 = 0.269, P < 0.001) with VSI ( P = 0.035) and neurological deficits ( P < 0.001) as significant independent predictors. Conclusions: Visuospatial inattention at acute stroke has an independent impact on long‐term functional outcomes. Early recognition may enable targeted rehabilitative interventions.